Knowledge, Attitude, and Practice of Biosafety Guidelines among Dental Undergraduates during COVID-19 Pandemic at a Dental Institution in North Karnataka – An Institution-Based Cross-Sectional Study - Vaishnavi A. Nidarkar; Zameera Naik; S Lokesh Kumar; Anand Badavannavar; Muskan D. Hinduja; Ram Surath Kumar (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Coronavirus Disease 2019 (COVID-19) pandemic had universally affected every field of health sciences with dentistry being no exception. The current study was planned to assess the preparedness of dental undergraduates to deal with patients during the COVID-19 pandemic. Objective: To assess the knowledge, attitude, and practice of biosafety practices during COVID-19 pandemic among the dental undergraduates. Methods: The knowledge, attitude, and practices of 262 dental undergraduates (third year, final year) including interns were evaluated using a self-designed, prevalidated questionnaire. Chi-square test was used to compare the responses among the undergraduates with P < 0.05 set as statistically significant. Results: The study revealed that 90.8% of undergraduates were aware about the term biosafety and 81.3% were aware about the practices to be followed when handling COVID-19 patients. In total, 85.9% considered that biosafety guidelines were applicable for doctors, assistants, and patients. Conclusion: The majority of undergraduates were highly knowledgeable and aware of biosafety regulations and signs/symptoms of COVID-19. Among the three categories, final-year undergraduates had maximum knowledge of the guidelines, followed by interns and third-year undergraduates.